Solve the following equation:
$8 + 9\sqrt {(3x - 1)(x - 2)} = 3{x^2} - 7x$
Answer
Verified
510.6k+ views
Hint: To make such an equation simple, multiply the expressions written inside the square root and do some operations to make the expression written inside the square root and the right hand side the same.
Complete step-by-step answer:
As, the given equation is
$8 + 9\sqrt {(3x - 1)(x - 2)} = 3{x^2} - 7x$ ………. (1)
First, we multiply the expressions written inside square root of equation 1
$8 + 9\sqrt {3{x^2} - 7x + 2} = 3{x^2} - 7x$ ………… (2)
As, we can see that the expression inside the square root will be the same as the expression on the other side of the equation, if we make a few adjustments.
In this case, we had to add 2 to both sides to get the required equation. So, adding 2 both side in the equation (2), we get
$10 + 9\sqrt {3{x^2} - 7x + 2} = 3{x^2} - 7x + 2$
Now, we can see that there are common terms on both sides of the equation so to simplify the equation, we take the common terms as a variable.
Let \[3{x^2} - 7x + 2 = {t^2}\] …………… (3)
Therefore, our equation reduces to
$10 + 9t = {t^2}$ ………….. (4)
Now, equation 4 can be easily solved as it reduces to a quadratic equation.
Solving equation 4 by factorisation,
$
\Rightarrow {t^2} - 9t - 10 = 0 \\
\Rightarrow {t^2} - 10t + t - 10 = 0 \\
\Rightarrow t(t - 10) + 1(t - 10) = 0 \\
\Rightarrow (t + 1)(t - 10) = 0 \\
\Rightarrow t = - 1,10 \\
$
We get two values of t, so from equation 3,
$ \Rightarrow 3{x^2} - 7x + 2 = {t^2}$
When \[t = - 1\], then
$ \Rightarrow 3{x^2} - 7x + 2 = {( - 1)^2}$
Solving the equation, we get
$ \Rightarrow 3{x^2} - 7x + 1 = 0$
Solving the above quadratic equation using the quadratic formula
$
\Rightarrow x = \dfrac{{7 \pm \sqrt {49 - 4(3)(1)} }}{{2(3)}} \\
\Rightarrow x = \dfrac{{7 \pm \sqrt {37} }}{6} \\
$
Also, when $t = 10$;
$ \Rightarrow 3{x^2} - 7x + 2 = {(10)^2}$
Solving the equation using factorisation, we get
$
\Rightarrow 3{x^2} - 7x - 98 = 0 \\
\Rightarrow 3{x^2} - 21x + 14x - 98 = 0 \\
\Rightarrow 3x(x - 7) + 14(x - 7) = 0 \\
\Rightarrow (3x + 14)(x - 7) = 0 \\
\Rightarrow x = - \dfrac{{14}}{3},7 \\
$
Hence, the values of x are $\dfrac{{7 - \sqrt {37} }}{6},\dfrac{{7 + \sqrt {37} }}{6}, - \dfrac{{14}}{3}$ and $7$.
Note: In such types of problems, we have to simplify the equation in such a way that the whole equation can be represented by another variable but in a simpler form which is easily solvable.
Complete step-by-step answer:
As, the given equation is
$8 + 9\sqrt {(3x - 1)(x - 2)} = 3{x^2} - 7x$ ………. (1)
First, we multiply the expressions written inside square root of equation 1
$8 + 9\sqrt {3{x^2} - 7x + 2} = 3{x^2} - 7x$ ………… (2)
As, we can see that the expression inside the square root will be the same as the expression on the other side of the equation, if we make a few adjustments.
In this case, we had to add 2 to both sides to get the required equation. So, adding 2 both side in the equation (2), we get
$10 + 9\sqrt {3{x^2} - 7x + 2} = 3{x^2} - 7x + 2$
Now, we can see that there are common terms on both sides of the equation so to simplify the equation, we take the common terms as a variable.
Let \[3{x^2} - 7x + 2 = {t^2}\] …………… (3)
Therefore, our equation reduces to
$10 + 9t = {t^2}$ ………….. (4)
Now, equation 4 can be easily solved as it reduces to a quadratic equation.
Solving equation 4 by factorisation,
$
\Rightarrow {t^2} - 9t - 10 = 0 \\
\Rightarrow {t^2} - 10t + t - 10 = 0 \\
\Rightarrow t(t - 10) + 1(t - 10) = 0 \\
\Rightarrow (t + 1)(t - 10) = 0 \\
\Rightarrow t = - 1,10 \\
$
We get two values of t, so from equation 3,
$ \Rightarrow 3{x^2} - 7x + 2 = {t^2}$
When \[t = - 1\], then
$ \Rightarrow 3{x^2} - 7x + 2 = {( - 1)^2}$
Solving the equation, we get
$ \Rightarrow 3{x^2} - 7x + 1 = 0$
Solving the above quadratic equation using the quadratic formula
$
\Rightarrow x = \dfrac{{7 \pm \sqrt {49 - 4(3)(1)} }}{{2(3)}} \\
\Rightarrow x = \dfrac{{7 \pm \sqrt {37} }}{6} \\
$
Also, when $t = 10$;
$ \Rightarrow 3{x^2} - 7x + 2 = {(10)^2}$
Solving the equation using factorisation, we get
$
\Rightarrow 3{x^2} - 7x - 98 = 0 \\
\Rightarrow 3{x^2} - 21x + 14x - 98 = 0 \\
\Rightarrow 3x(x - 7) + 14(x - 7) = 0 \\
\Rightarrow (3x + 14)(x - 7) = 0 \\
\Rightarrow x = - \dfrac{{14}}{3},7 \\
$
Hence, the values of x are $\dfrac{{7 - \sqrt {37} }}{6},\dfrac{{7 + \sqrt {37} }}{6}, - \dfrac{{14}}{3}$ and $7$.
Note: In such types of problems, we have to simplify the equation in such a way that the whole equation can be represented by another variable but in a simpler form which is easily solvable.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE